Access to Diabetes Self-Management Education in a Rural State: A GIS Analysis - Barbara Ann Graves; Elena Thompson; Grace Liu; Jane Kunberger; Laura Canaday; Brooke Bambis (Rural Nurse Organization; Binghamton University, 2019)
Background: Diabetes is a major cause of mortality and morbidity in the state of Alabama. Research has demonstrated geographical disparities in diabetes outcomes and access to healthcare service. Supporting behavior changes through diabetes self-management education (DSME) has been shown to improve diabetes outcomes. Purpose: The overall purpose of this study was to empirically measure and display spatial patterns of potential geographical accessibility of the Alabama populations to DSME services. Geographic information systems (GIS) technology was used to empirically and visually examine spatial relationships between variables related to diabetes and access to DSME services. The specific aims were to: (1) Determine the percentage of the Alabama population with geographical access to DSME services within 30 and 60minutes of travel time; (2) Determine the percentage of the population with access by age, sex, race, rural status, and SES. Method: A retrospective cohort, descriptive quantitative study DESIGN was used. GIS and U.S. Census Bureau data provided visual identification and empirical measures of distance and access. Findings: GIS analysis provided percentages of Alabama's total population with access to DSME at 30 and 60-minute travel time and maps allowed visualization of DES service coverage areas. Analysis showed that 66.3% and 94.1% of the total Alabama population were within a 30 and 60-minute travel time to a DSME service location, respectively. While SES status had a minor effect on accessibility, the most noticeable disparity in equity of access was for those living in a rural setting. Only 44.1% of individuals in rural settings had 30-minute access to a facility, whereas 81.7% of individuals in an urban setting had 30-minute access. DISCUSSION: Timely access to the best practice of DSME is essential in reducing diabetes mortality and disparities. Social justice requires the reversal of healthcare disparities created by geographical and social inequalities through better distribution of resources. Healthcare policy can change DSME locations to increase access and decrease mortality. DOI: http://dx.doi.org/10.14574/ojrnhc.v19i2.575